2012
DOI: 10.1175/jpo-d-11-0170.1
|View full text |Cite
|
Sign up to set email alerts
|

Declining Oxygen in the Northeast Pacific*

Abstract: Climate models predict a decrease in oceanic dissolved oxygen and a thickening of the oxygen minimum zone, associated with global warming. Comprehensive observational analyses of oxygen decline are challenging, given generally sparse historical data. The Newport hydrographic (NH) line off central Oregon is one of the few locations in the northeast Pacific with long oxygen records. Good quality data are available here primarily in two time blocks: 1960–71 and 1998–present. Standard sampling extends from midshel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 24 publications
2
70
0
Order By: Relevance
“…Deploying gear in the ocean involves some risk, as described for gliders by Brito et al (2014), whose view is based on many users new to gliders and is therefore rather bleak. My opinion is that more experienced glider operators have better performance, as must be the case for the glider programs that have been gathering data continuously for several years , Perry et al 2008, Todd et al 2011a, Pierce et al 2012, Pelland et al 2013, Mazzini et al 2014, Johnston & Rudnick 2015. The optimistic view is 10 August 2015 14:1 that ocean scientists willing to make an investment can approach the performance of experienced glider operators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deploying gear in the ocean involves some risk, as described for gliders by Brito et al (2014), whose view is based on many users new to gliders and is therefore rather bleak. My opinion is that more experienced glider operators have better performance, as must be the case for the glider programs that have been gathering data continuously for several years , Perry et al 2008, Todd et al 2011a, Pierce et al 2012, Pelland et al 2013, Mazzini et al 2014, Johnston & Rudnick 2015. The optimistic view is 10 August 2015 14:1 that ocean scientists willing to make an investment can approach the performance of experienced glider operators.…”
Section: Discussionmentioning
confidence: 99%
“…One application is to use gliders and satellite measurements to improve estimates of primary productivity ( Jacox et al 2015). Glider observations off Oregon have documented the declining levels of dissolved oxygen in coastal waters (Pierce et al 2012, Adams et al 2013). Continuing work is addressing the warm anomalies that have appeared throughout the eastern North Pacific during 2014-2015 (Figure 3).…”
Section: Large Scalesmentioning
confidence: 99%
“…Mesopelagic fishes in the Southern California bight area have declined >60% in abundance since the 1980s in association with increasing deep-water hypoxia due to climate change [64]. Further projected expansion of oxygen minimum zones (OMZ) is expected to have significant ecosystem impacts [65][67]. Warming temperatures and OMZ expansion have facilitated invasion of the California Current by jumbo squid ( Dosidicus gigas ) since the late 1990s.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies based either on direct observations or modeling have demonstrated that subsurface water in the open ocean has decreased in DO content in recent decades, possibly owing to reduced seawater ventilation under global warming (Ono et al, 2001;Deutsch et al, 2006;Whitney et al, 2007;Pierce et al, 2012;Takatani et al, 2012). Obviously, an input of offshore seawater with a lower DO yet higher nutrients and AOU exacerbates coastal eutrophication and spreads the hypoxia.…”
Section: Increasing Nutrients Yet Decreasing Do Under Reduced Ventilamentioning
confidence: 99%